Egalitarian da’wah as a da’wah strategy - Fuat Rejeki; Ali Murtadho; Agus Riyadi; Agus Nurhadi; Windy Ernaeny (Faculty of Dakwah and Communication, Walisongo State Islamic University, 2026)
Purpose - This study aims to analyse da‘wah strategies relevant to Muslim minority communities in Krajan, Kalimanggis, emphasising relational equality between da‘i and mad‘u, a dialogical, humanistic, and non-coercive approach, as well as the utilisation of basic needs fulfilment as a contextual medium for da‘wah. Method - This study employed a qualitative method with an ethnographic approach to understand the meanings attributed by religious leaders, Muslims, and non-Muslims to da‘wah practices, particularly the egalitarian da‘wah strategy, da‘wah bil ḥāl, and socially inclusive da‘wah. A sociological perspective was utilised to analyse religion as a social reality related to social structures, interactions, and community dynamics (Hasni, 2023). Data were collected through in-depth interviews and participant observation with eight respondents. These respondents included Muslim community leaders, ustadz/religious figures from outside the local area who had established majlis taklim, Islamic activists in Dusun Krajan, non-Muslim religious leaders, converts to Islam, respected community elders, and members of the Muslim youth organisation (karangtaruna). Result - This study indicates that the Muslim minority community in Dusun Krajan faces socio-economic limitations, limited access to religious education, and vulnerability in social relations within a predominantly non-Muslim environment, rendering conventional da‘wah less effective. The originality of this research lies in the formulation of egalitarian da‘wah as a contextual and adaptive strategy, emphasising relational equality between da‘i and mad‘u, a social–humanistic approach through the fulfilment of basic needs, and conflict management based on dialogue and empathy. The findings suggest that egalitarian da‘wah functions not only as a medium for transmitting Islamic teachings but also as a mechanism— —for strengthening social cohesion and restoring social relations, thereby supporting the sustainability of religious life and social harmony amongst Muslim minority communities. Implications – The implications of this study lie in reinforcing the perspective of da‘wah as a contextual and relational social practice within da‘wah studies and the sociology of religion, particularly amongst Muslim minority communities. Practically, the findings serve as a reference for da‘i and da‘wah institutions in designing dialogical, humanistic, and basic-needs-based da‘wah strategies to strengthen social cohesion and interfaith harmony. Originality/Value – This study presents egalitarian da‘wah as a contextual model for Muslim minority communities, emphasising relational equality, social–humanistic approaches, and interfaith dialogue. It positions da‘wah not merely as the transmission of religious teachings, but as a mechanism for strengthening social cohesion and restoring social relations, which is relevant for sustaining religious life and social harmony. *** Tujuan - Penelitian ini bertujuan menganalisis strategi dakwah yang relevan bagi masyarakat Muslim minoritas di Krajan, Kalimanggis, dengan menekankan kesetaraan relasional antara da’i dan mad’u, pendekatan dialogis, humanis, dan non-koersif, serta pemanfaatan pemenuhan kebutuhan dasar sebagai media dakwah yang kontekstual. Metode - Penelitian ini menggunakan metode kualitatif dengan pendekatan etnografi untuk memahami pemaknaan para tokoh agama, umat Muslim, dan non-Muslim terhadap praktik dakwah, khususnya strategi dakwah egaliter, dakwah bil ḥāl, dan dakwah sosial-inklusif. Pendekatan sosiologis digunakan untuk menganalisis agama sebagai realitas sosial yang berkaitan dengan struktur, interaksi, dan dinamika masyarakat (Hasni, 2023). Data diperoleh melalui wawancara mendalam dan observasi partisipatif terhadap 8 responden. Mereka adalah tokoh masyarakat muslim, para ustadz/ tokoh agama dari luar lingkungan yang telah mendirikan majelis taklim, pejuang agama Islam di dusun Krajan, tokoh agama non Muslim, mualaf, warga yang dituakan, dan karangtaruna muslim. Hasilnya menunjukkan bahwa kegiatan keagamaan seperti pengajian rutin, momentum Ramadhan, Idul Adha, dan perayaan hari besar Islam menjadi sarana efektif dalam membangun jaringan sosial serta pemenuhan kebutuhan dasar masyarakat Muslim di Krajan, Kalimanggis. Hasil - Kajian ini menunjukkan bahwa masyarakat Muslim minoritas di Dusun Krajan menghadapi keterbatasan sosial ekonomi, rendahnya akses pendidikan keagamaan, serta kerentanan relasi sosial dalam lingkungan mayoritas non-Muslim, sehingga dakwah konvensional cenderung kurang efektif. Kebaruan penelitian ini terletak pada perumusan dakwah egaliter sebagai strategi dakwah yang kontekstual dan adaptif, yang menekankan kesetaraan relasional antara da’i dan mad’u, pendekatan sosial-humanis melalui pemenuhan kebutuhan dasar, serta pengelolaan konflik berbasis dialog dan empati. Temuan ini menunjukkan bahwa dakwah egaliter tidak hanya berfungsi sebagai media transmisi ajaran Islam, tetapi juga sebagai mekanisme penguatan kohesi sosial dan pemulihan relasi sosial, sehingga relevan dalam mendukung keberlanjutan kehidupan keagamaan dan harmoni sosial masyarakat Muslim minoritas. Implikasi – Implikasi penelitian ini pada penguatan perspektif dakwah sebagai praktik sosial yang kontekstual dan relasional dalam studi dakwah dan sosiologi agama, khususnya pada masyarakat Muslim minoritas. Secara praktis, temuan ini menjadi rujukan bagi da’i dan lembaga dakwah dalam merancang strategi dakwah dialogis, humanis, dan berbasis pemenuhan kebutuhan dasar guna memperkuat kohesi sosial dan harmoni antarumat beragama. Orisinalitas/Nilai – Penelitian ini mengungkap dakwah egaliter sebagai model dakwah kontekstual bagi masyarakat Muslim minoritas yang menekankan kesetaraan relasional, pendekatan sosial-humanis, dan dialog lintas agama. Penelitian ini memposisikan dakwah tidak hanya sebagai transmisi ajaran, tetapi sebagai mekanisme penguatan kohesi sosial dan pemulihan relasi sosial yang relevan bagi keberlanjutan kehidupan keagamaan dan harmoni sosial.